Residents’ Satisfaction with Public Services Rendered at Tambon Dongklang Administrative Organization in Chaturaphakphiman District, Roi Et Province - Techapoonyo(Krajai), Phraboonying; Piriyasing, Udom (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study residents’ satisfaction with public services rendered, 2) to draw comparisons between their satisfaction as such and variables of their different genders, ages and educational qualifications, and 3) to examine suggestions for enhancing public services at at Tambon Donklang Administrative Organization in Chaturaphak Phiman district of Roi Et. The sampling groups employed for the quantitative research comprised 374 legible voters in its authorized constituencies. The research instrument was the five-rating scale questionnaire. The statistics utilized for processing data embraced: means standard deviations (S.D.), t-tests, F-tests (0ne-way ANOVA) and LSD (Less Significant Difference). As with the qualitative research, key informants were village headman chiefs, nurses and public health volunteers to the village, numbering eight subjects. The instrument used for data collection was the semi- constructed interview form. Contents were analyzed and presented in the descriptive manner. The results of the research showed that : 1) Residents’ satisfaction with public services rendered at the organization mentioned above have been rated at the ‘high’ scales both in the overall aspect and a single one. 2) The comparative hypothesis testing results have shown no significant differences between their satisfaction and the target variables, thereby not being in conformity with the established hypotheses. 3) Residents’ suggestions for enhancing public services rendered at their organization have been recommended in the descending order of first three frequencies. First, equal public services ought to be rendered much more than they have been in the regular basis in every area. Next, the organization should provide public disaster relief equipment and machinery so as to suffice to render services to residents. Last, traffic surface-obstructed objects on the main roads should be tackled rapidly.